2009
DOI: 10.2174/1874199100903010026
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Linear Short-Chain Phosphazene-Na+ Complexes

Abstract: In this work, we study simples phosphazenes models, such as R-[R 2 P=N] n -X, with (X = H, F, OH), (R= H, F) and (n = 1, 2 and 3) with an attempt to answer the type of Natural Hybrid Orbital (NHO) able to form this -bond in the phosphazene-Na + complex and the Na + effect on the geometry and the electronic distribution of the studied molecules by using the HF and DFT studies of electronics, molecular structures and Natural Bond Orbital (NBO) analysis. The substituent effect of the fluorine atom acceptor and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Aligning with the work reported by Chaplin et al, a similar interaction has been described in short linear chlorophosphazenes . These interactions can also correlate with the density functional theory (DFT) studies of bonding environments described for the cyclic and polymeric models in stage 2. …”
Section: Introductionmentioning
confidence: 82%
“…Aligning with the work reported by Chaplin et al, a similar interaction has been described in short linear chlorophosphazenes . These interactions can also correlate with the density functional theory (DFT) studies of bonding environments described for the cyclic and polymeric models in stage 2. …”
Section: Introductionmentioning
confidence: 82%
“…In this series of cyclic phosphazenes (NPX 2 ) 3 with X = H, Br, Cl and F, all identical PN bonds lengths obtained is a sign of aromaticity in this compounds. Used Quantum chemical calculations in order to find the effect of substitution halogens atoms in PN bonds; Abdellatif et al [60] have reported that the PN bond lengths in short linear phosphazenes decrease with increasing the electronegativity of (R 3 PNH, R 3 PNF and R 3 PNOH with R=H, F). Sabzyan et al have reported that the PN bond lengths in the cyclic phosphazenes decrease with increasing the electronegativity of the halogen substituent on the phosphorus atom [57].…”
Section: Structural Datamentioning
confidence: 99%
“…Previous computational efforts have primarily focused on analyzing the experimentally proven products in Scheme , , assuming the validity of the proposed S N 1 mechanism. Although computational analysis of the discrete polymer, cyclic compounds, and monomer has been performed, ,, , the role of [PCl 2 N] 3 in the ROP and RR equilibrium polymerization has never been systematically addressed using QM calculation methods. Here, we investigate the ROP mechanism starting with two and three [PCl 2 N] 3 rings by systematically mapping reaction pathways on the potential energy surface (PES), without assuming a predetermined mechanism.…”
Section: Introductionmentioning
confidence: 99%